Efek Polimorfisme Terhadap Kerentanan dan Tatalaksana Tuberkulosis Paru - Rusdi, M.; Adenina, Syarinta (Universitas Ciputra Surabaya, 2024)
Pulmonary tuberculosis (TB) remains the second leading cause of death from a single infectious agent. The number of people with pulmonary TB in the world still increased, and TB treatment success percentage in Indonesia has not reached the target until now. Genetic polymorphisms are defined as DNA variations seen in ≥1% of the population. The study of genetic polymorphisms can help identify disease risk, predict drug efficacy and safety, and determine the right chemotherapeutic agent with a dose that suits each patient. Various genetic polymorphisms associated with pulmonary TB susceptibility have been found, including polymorphisms of the NRAMP1, HLA-DRB1, vitamin D receptor, TNF-α, and IFN-γ genes. In addition, several genetic polymorphisms associated with TB treatment were also found, such as SLCO1B1, NAT2, SLC2A9, and ABCB1 genes. Detection of genetic polymorphisms in each individual can help predicts TB risk and improve TB treatment success and reduce side effects that may occur due to TB treatment.